PENGEMBANGAN MEDIA BK INTERAKTIF BERBASIS MACROMEDIA FLASH UNTUK MENANAMKAN NILAI KARAKTER PADA SISWA SD - Herwinda Putri Daniswari dan Drajat Edy Kurniawan (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
AbstractThe purpose of this study was to produce a product in the form of Macromedia Flash-based Interactive Guidance and Counseling Media to Embed Character Values in Elementary Students. This research is motivated by the importance of providing Guidance and Counseling services by using interactive media to instill character values in elementary students. The method used in this research is R&D. Operationally the R&D research steps are described in three stages, namely the survey stage, the model development stage, and the model testing stage. In the initial stage a survey was conducted which was useful to (1) identify the scope of the problem; (2) identify areas of guidance and counseling services. The second stage is the stage of media development and testing. The third stage is the product validation test stage. At this stage the testing of interactive guidance and counseling media using macromedia flash was conducted for elementary school students. The results of this study are in the form of Macromedia Flash-based Interactive Guidance and Counseling Media products to Embed Character Values in Elementary Students.Keyword : Interactive Guidance and Counseling Media, Macromedia Flash, Character Values